ANALISIS TERHADAP LARANGAN PRAKTIK INSIDER TRADING DI PASAR MODAL - Tandi Pada Palayukan (USU LAW JOURNAL, 2013)
The existence of capital market is fundamental in economic development. Capital market not only functions to raise fund and to allocate public fund, but also plays an imfortent role in word business development. Insider trading practice is very potential to accur in capital market. The characteristic of insider trading practice in the Indonesian Capital Market is that it was done by manipulating the market. Did not regulated the element resulted from the action or loss. The provision of prohibiting insider trading, narrowed the meaning of “insider” in trust-based relationship only. Insider trading controlled by Bapepam-LK in coordination and integration with OJK that the control of insider trading is not under the Ministry of Finance anywere. The law on capital market needs to be revised to determine the element of loss inflicted by insider trading. It is regulating “insider” should be extended that it is not focusing on the trust-based relationship only and controlling capital market can be efficiently and integratedly.